From Vulnerability to Adaptation: Identifying Resilient Practices for Sustainable Dragon Fruit Farming in a Changing Climate - Wahyuningsih; Fadilah Nurdin; Megawati; Mirnatul Qinayah; Daeva Mubarika Raisa (FAKULTAS PERTANIAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
This study aims to determine the effect of climate change on the productivity of dragon fruit crops in Sukamaju Village, Tellulimpoe District, Sinjai Regency. The study used a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Informants consisted of dragon fruit farmers, community leaders, and relevant stakeholders. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing systematic conclusions. The results showed that climate change, rainfall, temperature, and sunlight significantly affect the growth and yield of dragon fruit. Climate fluctuations cause production instability, reduce productivity, and affect fruit quality, even when land and cultivation techniques are adequate. This situation requires serious attention from farmers and related parties to implement adaptation measures to maintain optimal and stable production. Adaptation strategies that can be implemented include irrigation management, selecting climate-resistant varieties, timely fertilization, and regular weather monitoring. With these measures, the productivity and quality of dragon fruit crops in Sukamaju Village can increase, support local agribusiness development, raise farmer income, and meet local and national market demand. This research confirms that climate change is a crucial factor in the management of dragon fruit crops and can serve as the basis for policy recommendations and adaptive agricultural practices for sustainable agribusiness in Sinjai Regency